ANALISIS PENGARUH KETERLIBATAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI (Survei pada Pegawai Dinas Koperasi dan Tenaga Kerja Kabupaten Boyolali) - Suprihatmi Sri Wardiningsih, Agus Handoyo, Alwi Suddin & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
This research aims to analyze the influence of work involvement andorganizational culture on performance clerk with organizational commitmentas intervening variable. This study used a survey method, the type of datathe data used was qualitative and quantitative data, the source data used theprimary data and secondary data. The population in this study are allemployees of the Department of Cooperatives and labor Boyolali Regencytotaling 76 employees. The number of samples in this research as much as76 employees, so it is a research census. Methods of data collection wereused: questionnaire. Technique of data analysis used the test of validity,reliability test, test the assumptions of classical, and path analysis. Theresults of the analysis of the data obtained: the conclusion that theinvolvement of the workforce and organizational culture organizationalcommitment significantly to influential officials of the Department ofCooperatives and labor Boyolali Regency. Work engagement, organizationalculture and organizational commitment effect significantly to the performanceof the employees of the Department of Cooperatives and labor BoyolaliRegency. Organizational commitment and job involvement to mediate theinfluence of organizational culture on performance clerk Department ofCooperatives and labor Boyolali Regency.Keywords: job engagement, organizational culture, organizationalcommitment, performance of employees